Breast Milk Metabolomic Profile Is Associated With Maternal Overweight/Obesity Status or Adherence to Mediterranean Diet and Infant Weight Gain During the First Month of Lactation - Catalina A. Pomar; Petr Zouhar; María DeLucas; Tomas Cajka; Pilar Cobo; María Victoria Jiménez‐Cabanillas; Pere Bibiloni; Jan Kopecky; Andreu Palou; Francisca Serra; Juana Sánchez; Catalina Picó (Food Frontiers)
ABSTRACT Breast milk provides a wide range of nutritional and bioactive components crucial for infant growth and development during lactation, ultimately influencing future health outcomes. Here, we used untargeted metabolomics to identify differences in the breast milk metabolome related to maternal overweight/obesity and diet, assessing their influence on infant weight gain in the first month of lactation. Anthropometric data from 52 lactating mother–infant pairs were collected at birth and 1 month postpartum, along with breast milk samples. Information about food consumed the day before milk sampling (24‐h questionnaire) was collected, and a food frequency questionnaire was completed. Our findings reveal that mothers with overweight/obesity had greater lactose levels (p = 0.025) and lower levels of orotic acid (p = 0.002), 3‐indoxyl sulfate (p = 0.027), heneicosanoic acid (p = 0.040), and N1‐methylguanosine (p = 0.046) in milk than normal‐weight mothers. Notably, reduced orotic acid levels were associated with a greater infant weight gain during this period. Furthermore, mothers with a low adherence to the Mediterranean diet showed lower levels of citric acid (p = 0.041), N6‐succinyladenosine (p = 0.043), uric acid (p = 0.034), and eicosenoic acid (p = 0.035), and higher levels of acylcarnitine C6:0 (p = 0.041) than mothers with a medium/high adherence. Besides orotic acid, other milk metabolites were related to infant weight gain during this period, with maternal fruit and fish consumption (p = 0.015 and p = 0.017) emerging as the most influential dietary factor for an adequate early infant growth trajectory. None of the metabolites identified remained statistically significant after multiple‐comparisons adjustment. Present results, showing how maternal diet and obesity can affect breast milk metabolites and infant growth, offer insights to improve lactation‐feeding practices and support healthy infant development.